1996
DOI: 10.1128/jvi.70.2.1100-1108.1996
|View full text |Cite
|
Sign up to set email alerts
|

Human monoclonal antibody 2G12 defines a distinctive neutralization epitope on the gp120 glycoprotein of human immunodeficiency virus type 1

Abstract: We have isolated and characterized human monoclonal antibody 2G12 to the gp120 surface glycoprotein of human immunodeficiency virus type 1 (HIV-1). This antibody potently and broadly neutralizes primary and T-cell line-adapted clade B strains of HIV-1 in a peripheral blood mononuclear cell-based assay and inhibits syncytium formation in the AA-2 cell line. Furthermore, 2G12 possesses neutralizing activity against strains from clade A but not from clade E. Complement-and antibody-dependent cellular cytotoxicity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
411
1
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,042 publications
(423 citation statements)
references
References 62 publications
10
411
1
1
Order By: Relevance
“…At this early stage of investigation, all antibodies to GDEs of the HIV-1 envelope protein are informative; however, antibodies to the V1/V2 domain of gp120 are of particular interest. First, the V1/V2 domain contains the GDEs recognized by several bN-mAbs (e.g., PG9, PG16, CH01-4, PGT145) (Walker et al, 2009(Walker et al, , 2011Pejchal et al, 2011;Sanders et al, 2002;Trkola et al, 1996;Mouquet et al, 2012;Bonsignori et al, 2011). Second, nonneutralizing antibodies to the V1/V2 domain represent the only antibody response found to correlate with protection in the RV144 HIV vaccine trial, which included immunization with the ALVAC-HIV canarypox vector vaccine (vCP1521) and the AIDSVAX B/E recombinant gp120 subunit vaccine (Berman, 1998;Berman et al, 1999;Rerks-Ngarm et al, 2009;Haynes et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…At this early stage of investigation, all antibodies to GDEs of the HIV-1 envelope protein are informative; however, antibodies to the V1/V2 domain of gp120 are of particular interest. First, the V1/V2 domain contains the GDEs recognized by several bN-mAbs (e.g., PG9, PG16, CH01-4, PGT145) (Walker et al, 2009(Walker et al, , 2011Pejchal et al, 2011;Sanders et al, 2002;Trkola et al, 1996;Mouquet et al, 2012;Bonsignori et al, 2011). Second, nonneutralizing antibodies to the V1/V2 domain represent the only antibody response found to correlate with protection in the RV144 HIV vaccine trial, which included immunization with the ALVAC-HIV canarypox vector vaccine (vCP1521) and the AIDSVAX B/E recombinant gp120 subunit vaccine (Berman, 1998;Berman et al, 1999;Rerks-Ngarm et al, 2009;Haynes et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Second, many of the conserved envelope regions might not be accessible due to high levels of glycosylation in the variable loops and relatively high mobility, which is sometimes referred to as the 'glycan shield' [6,46,47]. Counter intuitively, the monoclonal antibodies 2G12, PG9 and PG16, which neutralize HIV-1 from multiple clades, bind to glycosyl moieties or V2 and V3 of gp120 [48,49]. Nonetheless, the sequence variability, glycosylation and mobility make the envelope a moving target, which complicates the search for molecules that bind with high specificity.…”
Section: Reviewmentioning
confidence: 99%
“…Entry inhibitors have been discovered by a number of different strategies: (i) monoclonal antibodies; (ii) phage display; (iii) small molecule screening; (iv) structure-based drug design. Monoclonal antibodies that bind specifically to the HIV envelope (and block entry) can be found in patients exposed to HIV [48]. Phage display is performed by exposing a library of phage expressing short peptide regions (there are similar techniques that employ bacteria or yeast libraries) to the HIV envelope or CD4 and CR [89].…”
Section: Box 2 Discovery Of Entry Inhibitorsmentioning
confidence: 99%
“…It has been reported that 2G12 neutralises A and B clade HIV-1 virus entry by recognition of a Manα1→2Man rich epitope on the exterior face of the gp120 protein (Binley et al, 2004;Scanlan et al, 2002). Monoclonal antibody (MAb) 2G12 can activate the complement system and display antibody dependent cellular cytotoxicity (ADCC) against virus infected cells (Trkola et al, 1996). Passive infusion of 2G12 combined with other neutralising antibodies including 2F5, protected macaques from a vaginal and intravenous challenge with SHIV (Baba et al, 2000;Mascola et al, 2000).…”
Section: G12mentioning
confidence: 99%